When Violence Hits the Religious Home: Raising Awareness about Domestic Violence in Seminaries and amongst Religious Leaders - McMullin, Steve; Nason-Clark, Nancy; Fisher-Townsend, Barbara; Holtmann, Cathy (2015)
The focus of this article by our research team looks specifically at the teaching of domestic violence classes in a seminary or religious context, as well as the ongoing professional education of religious leaders, such as pastors. It also considers ways to introduce therapeutic staff to the unique vulnerabilities of highly religious clients who have been abused or who act abusively. Based on data that we have collected at North American theological seminaries and in congregations, we explain some of the challenges of including instruction about domestic violence in a religious context.
Keywords: Training; Seminary; RAVE; Pastors; Domestic Violence; Clergy